Residents' preference for the management of green tides and its determinants: The evidence from Qingdao, China. (15th February 2023) - Xu, Zhihua; Meng, Wenchao; Li, Shuqin; Shan, Jingzhu
Abstract: Green tides, which cause serious harm to the marine ecological environment, have become a serious and recurrent environmental event in China. This paper investigates the residents' willingness to pay for the governance of green tides. The results show that residents' willingness to pay (WTP) for the complete disappearance of green tides and the restoration of coastal environment to the state before green tides reaches 68.59 CNY/a (US 9.85) on average. Additionally, the study uses self-identity and information concern to reflect the differences of residents' intrinsic characteristics and the onslaught of the extrinsic information to empirically analyze the sources of the preference differentials. Risk perception, moral norms, and self-efficacy are further introduced to observe the influence mechanism. The results indicate that moral norms are the most important factors affecting the WTP, and a direct relationship between information concern and residents' WTP is observed. Self-identity does not show a direct impact on residents' preference, however, has an indirect influence through moral norms and self-efficacy. This paper helps to increase individual pro-environmental behaviors and provides references for the management of green tides. Highlights: Green tides cause serious harm to the marine ecological environment. Investigates WTP of residents with different socioeconomic characteristics. Considers value evaluation from actual management measures adopted by government. Empirically analyzes the sources of differentials of residents' WTP. Provides references for the public participation in the management of green tides.